Pequenos trabalhadores: arte de rua nos vagões, causos dos trilhos e o (re)encontro identitário de um palhaço periférico - Geraldo, Guilherme Basilio [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work proposes to bring reflections about street art, in the São Paulo-SP Subway, with the scene performed by the comic duo Trupe dos Trilhos, Os Pequenos Trabalhadores. Transgressing academic language norms, based on the culture of the periphery and bringing RAPs as important references, the present monograph is the result of researching the stories of this troupe, reported here in the form of “stories”, from the perspective of a clown born and raised in Diadema. I will bring the methodology of this autonomous artistic process, along the lines of the practice of the clown figure in the wagons. Finally, I will raise important aspects of the surroundings of the presentations, Finally, I will raise important aspects of the surroundings of the presentations, such as the problems involving the safety of the subway company and the marginalization of artistic practice, and the peripheral identity of a clown being rediscovered, through the relationship with the public transit audience.

Este trabalho se propõe a trazer reflexões acerca da arte de rua, no Metrô de São Paulo-SP, com a cena realizada pela dupla cômica Trupe dos Trilhos, Os Pequenos Trabalhadores. Transgredindo normatividades acadêmicas de linguagem, fundamentada pela cultura de periferia e trazendo RAPs como importantes referências, a presente monografia é resultado da pesquisa de histórias desta trupe, relatadas aqui em forma de “causos”, partindo da perspectiva de um palhaço nascido e criado em Diadema. Trarei a metodologia desse processo artístico autônomo, aos moldes da prática da figura palhaça nos vagões. Por fim, levantarei aspectos importantes do entorno das apresentações, como as problemáticas envolvendo a segurança da companhia de metrô e a marginalização da prática artística, e a identidade periférica de um palhaço sendo redescoberta, por meio da relação com a plateia transeunte do transporte público.
Little workers: street art in the wagons, stories from the rails and the identity (re)encounter of a peripheral clown
Keywords: Arte de rua; Hip-hop; Metrô; Palhaços; Periferia